(3QSGdI aj CUhd Gdabgs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje EYde Cf YKeGf hYdjkG QVi Gddg JYGdi YfgeG ENJdaG ai GdLeY Hjf GdCNJjf hWFkG Hedc Gdjejf abGd Ydi hcGf GdCNP HeG jMQe Chdi EMJjGWkG s
(3BNQgG (B:s
(3hEf de jTJed YdjgG Hd Ydi eUdMI aEf cGf WQa GdaYd aGdaYd efOhH hEf cGf WQa GdJQc aGdaYd ecQhg JeJ GdQSGdI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3CUhd Gdabgs